2000
DOI: 10.1159/000012831
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits and Cardiovascular Risk in the Spanish Population: The DRECE Study (I)

Abstract: Backgrounds/Aims: To investigate dietary habits and their evolution with regard to cardiovascular risk status in Spain. Methods: Cross-sectional study performed in two phases in 1991 and 1996 in 43 primary care clinics. One thousand and two hundred people classified as ‘with cardiovascular risk’ and 600 ‘without risk’ were studied. Each participant answered a food frequency questionnaire. Results: The risk group did not change oil, cereals and dairy products consumption, decreased egg, legume and meat, and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
2
5
1
4
Order By: Relevance
“…The presence of one or more cardiovascular risk factors (obesity, hypertension, hypercholesterolaemia and diabetes) is not linked to a lower adherence to the MDP, although it has been reported that the Mediterranean diet protects against these diseases. However, it is probable that individuals with such problems had changed their diet in a healthier way as a result of medical advice or prescription, as it has been observed in the present study (data not shown) and in previous studies (Ballesteros-Pomar et al 2000).…”
Section: Discussionsupporting
confidence: 70%
“…The presence of one or more cardiovascular risk factors (obesity, hypertension, hypercholesterolaemia and diabetes) is not linked to a lower adherence to the MDP, although it has been reported that the Mediterranean diet protects against these diseases. However, it is probable that individuals with such problems had changed their diet in a healthier way as a result of medical advice or prescription, as it has been observed in the present study (data not shown) and in previous studies (Ballesteros-Pomar et al 2000).…”
Section: Discussionsupporting
confidence: 70%
“…Finally, red wine, generally consumed during meals, is the main alcohol intake and is relatively more prevalent with respect to other alcoholic beverages. Nevertheless, it is beyond doubt that there is no individual Mediterranean diet; in fact, some recent nutritional surveys showed that dietary habits of countries bordering the Mediterranean sea vary considerably and even inside the same country relevant differences in dietary pattern exist (Ballesteros-Pomar et al, 2000;Karamanos et al, 2002;Capita and Alonso-Calleja, 2003;Correa Leite et al, 2003;Bongard et al, 2004;Tur et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty of changing the dietary habits of diabetics, also observed in previous studies [1,22], may be explained by the fact that the diagnosis of this disease might have led to beliefs or even medical advice which is not always consistent with the intended intervention, making it more difficult to achieve many favorable changes. Thus, a low fat diet has been consistently used in Spain to treat patients with diabetes and other CVD risk factors, and despite the increasing evidence of the MeDiet effectiveness, its use in primary health care settings is still very low, since it takes a long time for evidence to filter through into practice.…”
Section: Discussionmentioning
confidence: 91%